Bank Deposit Guarantee Scope: Comparative Study - Hadi, Shahad; Ibrahim, ِAli (Journal of Legal Sciences, 2023)
The guarantee of deposits came in most countries as a result of the financial crises faced by the banks, as the role of the guarantee agencies does not end to the point of enabling the depositor to recover his deposit, but rather it is considered necessary to overcome crises and stabilize the banking system.The decisions related to the coverage determined by the types of guarantee are important, and it is required that these decisions be consistent with the policy of each guarantee to control and limit the negative effects that accompany deposit insurance, in order to face any risk that threatens deposits and confidence in them and to avoid any financial failures for the stability of the banking system and the protection of depositors’ rights. Bank deposit insurance systems are important, especially at the beginning of their inception, so they must be studied and accurate in terms of deposits covered by the guarantee and the deposit excluded from it, and identifying the persons who benefit from the amount of compensation and if the depositor dies or declares his bankruptcy, who are the beneficiaries of the compensation amount.